Study of Breathing-Related Metrics During Light Physical Activity - Aleid, Adham (British Journal of Healthcare and Medical Research, 2023)
The worldwide outbreak of the COVID-19 pandemic in 2020 has changed many social aspects of human behaviors. This new situation gave high significance to the concerning question and the everlasting debate about the influence of wearing facial masks on critical vital signs. This study aimed ‎to non-invasively explore the effect of wearing of the N95 facemask on physiological breathing-related measurements ‎during daily activities. Short physical exercise protocols were developed to mimic daily activities (i.e., ‎walking, climbing stairs, ‎etc.) in terms of exercise intensity and duration in a consistent ‎and controlled manner‎. The effect of wearing the N95 on breathing force and frequency, SPO2 and heart rates were measured at rest and during physical activities (i.e., pedaling on a stationary bicycle). Thirty-two subjects performed a total of four experimental setups to investigate the effect of two factors: N95 mask and physical activity. The main finding of this study is the significant increase in peak-to-peak breathing force ‎‎(i.e., Differential Breathing Force (DBF)) exerted by chest muscles in response to wearing an N95 mask at rest and during physical activity (p < 0.003 and p < 0.0003, respectively). Moreover, a significant slight SPO2 decrease was recorded during physical activity with N95 compared to non-mask (p < 0.0003). The proposed method of quantitatively measuring breathing forces ‎via a breathing belt was a noninvasive, reliable way of confirming the negative impact of using N95 masks on breathing, especially during physical activities.‎